Measurement on strain rate sensitivity properties of rice husk/ linear low density polyethylene (LLDPE) composites under various loading rates
The dynamic compression testing and static compression testing were performed using Split Hopkinson Pressure Bar (SHPB) apparatus and a conventional Universal Testing Machine (UTM), respectively. These two techniques were used to investigate the effect of strain rates towards the compressive properties of rice husk (RH) reinforced with linear low density polyethylene (LLDPE) composites. The SHPB results were initially verified and calibrated. The results show that all tested RH/LLDPE composites have a greater dependency towards the strain rate applied, where the yield stress, compression modulus, and compressive strength, were all proportionally increased as the strain rate increased. Besides, the effect of filler content, silane coupling agents and particle sizes of RH/LLDPE composites under a wide range of strain rates also investigated. It can be clearly seen that the introduction of rice husk filler into LLDPE matrix increased the composite’s compressive properties, including yield stress, compression modulus and compressive strength. It was also found that the filler content showed insignificant relationship with strain rate sensitivity and thermal activation volume. For the effect of silane coupling agent, the results indicate that compressive strength, stiffness properties and yield behaviour were improved for treated RH/LLDPE composites. Meanwhile, silane coupling agent showed significant relationship with strain rate sensitivity and thermal activation volume. As for the effect of particle size, it was found that the size of rice husk gave significant effects on the compressive properties of RH/LLDPE composites. The composites with smaller particle size has recorded higher compressive properties, in terms of yield strength, strength and stiffness as compared to composites with larger particle sizes. For the post damage analysis, the results show that applied strain rates affected the deformation behaviour of tested RH/LLDPE composites while at dynamic loading, the fracture surface analysis of the composites was examined. Overall, it can be concluded that these research finding can widen the scope of research area that related to the strain rate under dynamic loading for natural filler reinforced composites, and these RH/LLDPE composites also have the high potential to be applied in the industry application.